A Diversified Recruitment Approach Incorporating Social Media Leads to Research Participation Among Young Adult-Aged Female Cancer Survivors - Gorman, Jessica R. (Mary Ann Liebert, Inc., 2014)
Purpose: Cancer survivors in their adolescent and young adult (AYA) years are an understudied population, possibly in part because of the high effort required to recruit them into research studies. The aim of this paper is to describe the specific recruitment strategies used in four studies recruiting AYA-aged female cancer survivors and to identify the highest yielding approaches. We also discuss challenges and recommendations. Methods: We recruited AYA-aged female cancer survivors for two studies conducted locally and two conducted nationally. Recruitment strategies included outreach and referral via: healthcare providers and clinics; social media and the internet; community and word of mouth; and a national fertility information hotline. We calculated the yield of each recruitment approach for the local and national studies by comparing the number that participated to the number of potential participants. Results: We recruited a total of 534 participants into four research studies. Seventy-one percent were diagnosed as young adults and 61% were within 3 years of their cancer diagnosis. The highest-yielding local recruitment strategy was healthcare provider and clinic referral. Nationally, social media and internet outreach yielded the highest rate of participation. Overall, internet-based recruitment resulted in the highest number and yield of participants. Conclusion: Our results suggest that outreach through social media and the internet are effective approaches to recruiting AYA-aged female cancer survivors. Forging collaborative relationships with survivor advocacy groups' members and healthcare providers also proved beneficial.